MEMAHAMI PERILAKU ISTRI MELAYANGKAN CERAI GUGAT DI KABUPATEN BANYUWANGI - Mahmud, M. Amir (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
The phenomenon of divorce in the last decade in Banyuwangi has increased quite sharply. This paper wants to carefully analyze how the behavior of a wife who filed for divorce in the Religious Court of Banyuwangi Regency. This type of research is descriptive research taken from qualitative data in the form of field observations, interviews, and documentation as analytical material, so that the author can find important findings. The findings showed that the behavior of the wife filing for divorce can be seen from the presence of predisposing factors, catalyst factors and driving factors. These three factors also cause women to divorce more than once. This divorce can be viewed as a structure in which there are relationships that synchronically give rise to a phenomenon of divorce. Divorce is considered a social and natural behavior in society, with divorced wives getting happiness and peace.